UNGKAPAN METAFORIS BAHASA MELAYU TERNATE DI DESA SEA TUMPENGAN, SEA MITRA, DAN BUHA (METAPHORICAL EXPRESSIONS OF TERNATE MALAY IN SEA TUMPENGAN VILLAGE, SEA MITRA VILLAGE, AND BUHA VILLAGE) - Vivi Nansy Tumuju (Balai Bahasa Sulawesi Utara, 2016)
The application of metaphorical expression malay ternate became daily expressions in the society. Expressions delivered are attempts to unite the cultural diversity of ternate with other residents. the users of malay ternate of ternate sub-ethnic who lived in the sea tumpengan village, sea mitra, and buha, contain many metaphorical expressions. the meanings of metaphorical expressions show the kinship and mindset of society of the ternate malay language speakers. it was found that metaphorical expression and the meaning contained in it is summed up in a few metaphorical expressions that have elements of reprimands, warnings, and advice. ternate malay language is rich with metaphorical expressions that have meaning manners, advice, ethics, religious norms, and legal norms. examples of metaphorical expression meaning reprimand delivered spontaneously in speaking to someone who does not have a permanent job or a lazy person. meaning of warning is a statement to anyone else who would do an activity and the person who will deliver the metaphorical expression already know the impact it will have. advice is delivered to the other party because of something that already does not look normal or have already exceeded the capacity that would be bad.